ISOLATION, PHYTOCHEMICAL ANALYSIS AND BIOLOGICAL STUDIES OF “WITHANIA SOMNIFERA” FRUITS OF DISTRICT BANNU, KHYBER PAKHTUNKHWA, PAKISTAN - Kalim Ullah; Nemat Ullah; Dr. Wahib Noor Khan (American Journals Publishing, 2022)
The current research aim with the study of Withania somnifera a best natural source of potent. This biologically important medicinal plant contain various natural product in all parts i.e.s in areal parts, flowers, leaves, stem and underground roots. The research project conducted for  determining and exploration of different natural products by qualitative phytochemiccal screening test from various factions. Current study support that the plant contain many natural product in different factions. The research confirmed important natural products are present in Hexane, Chloroform, ethyl acetate, butanol and water fraction and can be extracted easily by different methods.
Keywords: Physiochemical analysis; Withania somnifera; fruit and Bannu